Evidence-Based Practices as the Antidote to the Reading Crisis: A Case Against Alphabetic Phonics - Reagan Murnan (The Advocate, 2025)
The ongoing reading crisis in the United States necessitates a shift toward instructional practices that are firmly grounded in empirical research. This manuscript critiques the use of Alphabetic Phonics, not only for its reliance on multisensory techniques but also for its incorporation of instructional features that contradict the principles of Structured Literacy and explicit instruction—such as learning without failure, discovery learning, and loosely guided exploration. Drawing from decades of research, including findings from the National Reading Panel (2000) and contemporary meta-analyses, the paper argues that effective literacy instruction must prioritize direct, systematic, and evidence-based methods. The discussion examines how the instructional philosophy and program design of Alphabetic Phonics fail to provide the clarity, structure, and feedback needed by struggling readers, particularly those with dyslexia. Additionally, the manuscript critiques recent legislative decisions that permit at-risk educational funding and state licensure credentials to support programs lacking rigorous research validation. Ultimately, this work calls for literacy policies and instructional decisions to be anchored in evidence-based practices to ensure effective reading instruction for all students.
Keywords: Alphabetic Phonics; evidence-based practice; explicit instruction; structured literacy